Characterization of Toll-Like Receptor-4 (TLR-4) in the Spleen and Thymus of Swiss Albino Mice and Its Modulation in Experimental Endotoxemia - Chandrayee Ghosh; Biswadev Bishayi (Journal of Immunology Research)
Expression of innate immune receptors varies among organs and species and within different strains among the same species; thus, periodic classification of different pattern recognition receptors in the available strains is necessary to initiate different therapeutic approaches to combat inflammation. On characterization of TLR-4 in spleen and thymus of Swiss albino mice—with no reports of TLR-4 expression—induced with endotoxemia, it was found that the mode of expression varied among the organs at both mRNA and protein level in a time-dependent manner. Their functionality was verified by measuring proinflammatory and anti-inflammatory cytokines. In the in vitro study using isolated macrophages and lymphocytes from the same organs, the expression of TLR-4 after a shorter period of LPS stimulation was verified. The results substantiated the potent role of macrophage on LPS challenge compared to lymphocytes. The diverse pattern of TLR-4 expression on different cell population indicated their distinct functional activity in LPS-endotoxemia. It may be hypothesized that the expression patterns of TLR-4 could be different based on the anatomical localization and the varying bacterial milieu or bacterial endotoxin encountered in each anatomical location. Thus, blocking TLR-4 or administering IL-6 or IL-10 might impart protection against endotoxemia in the clinical field.